Family values: Ownership structure, performance and capital structure of Canadian firms - Michael R. King; Eric Santor (Bank of Canada, 2007)
This study examines how family ownership affects the performance and capital structure of 613 Canadian firms using a panel dataset from 1998 to 2005. In particular, we distinguish the effect of family ownership from the use of control-enhancing mechanisms. We find that freestanding family-owned firms with a single share class have similar market performance than other firms based on Tobin's q ratios, superior accounting performance based on ROA, and higher financial leverage based on debt-to-total assets. By contrast, family-owned firms that use dual-class shares have valuations that are lower by 17% on average relative to widely-held firms, despite having similar ROA and financial leverage. Finally, concentrated ownership by either a corporation or a financial institution does not significantly affect firm performance.
Keywords: G12; G15; 330; Financial markets; International topics; Familienunternehmen; Unternehmenswert; Kapitalstruktur; Fremdkapital; Rentabilität; Kanada